Pollution Characteristics and Source Analysis of Carbonaceous Components in PM2.5 in a Typical Industrial City - Liyan Ma; Dongmei Hu; Yulong Yan; Yueyuan Niu; Xiaolin Duan; Yafei Guo; Wanhua Li; Lin Peng (Aerosol and Air Quality Research)
Abstract Carbonaceous components are important components of fine atmospheric particulate matter (PM2.5) and can affect the local environment, climate, and human health. In this study, online observation data from September 1, 2022, to August 31, 2023, were used to analyze the carbonaceous components, namely, organic carbon (OC) and elemental carbon (EC), in PM2.5 in Jincheng, which is a typical industrial city. The OC and EC concentrations and annual average ratio of OC/EC in Jincheng were 5.54 µg m−3, 0.98 µg m−3, and 5.67, respectively. The concentration change in carbonaceous components shows strong seasonality and daily variation characteristics, and the influence of biomass combustion on carbonaceous components in winter cannot be ignored. OC was divided into primary organic carbon (POC) and secondary organic carbon (SOC) using the minimum R squared (MRS) method, and the highest and lowest amounts of SOC were generated in winter and summer, respectively. However, owing to the photochemical reaction that produces SOC in summer, the SOC/OC ratio was high. The high OC/EC ratio in summer was strongly dependent on the O3 concentration, proving that more SOC was formed through photochemical oxidation in summer, and multi-phase inversion may be the main method of SOC generation in winter. Correlation analysis between the carbonaceous components and gaseous pollutants in Jincheng showed that the carbon components in Jincheng City in autumn and winter were significantly influenced by industrial emissions, coal combustion emissions and vehicle emissions. Vehicle emissions were the main source of carbon components in Jincheng during summer. The formation of SOC was related to other VOCs emission sources. Our results show that carbon aerosol pollution in typical industrial cities, such as Jincheng, can be further alleviated by strengthening the control of vehicle exhaust emissions, fuel combustion, and biomass combustion.